Shaping pseudoneglect with transcranial cerebellar direct current stimulation and music listening - Picazio, Silvia; Granata, Chiara; Caltagirone, Carlo; Petrosini, Laura; Oliveri, Massimiliano (Frontiers in Human Neuroscience, 2015)
Non-invasive brain stimulation modulates cortical excitability depending on the initial activation state of the structure being stimulated. Combination of cognitive with neurophysiological stimulations has been successfully employed to modulate responses of specific brain regions. The present research combined a neurophysiological pre-conditioning with a cognitive conditioning stimulation to modulate behavior. We applied this new state-dependency approach to investigate the cerebellar role in musical and spatial information processing, given that a link between musical perception and visuo-spatial abilities and a clear cerebellar involvement in music perception and visuo-spatial tasks have been reported. Cathodal, anodal or sham transcranial cerebellar Direct Current Stimulation (tcDCS) pre-conditioning was applied on the left cerebellar hemisphere followed by conditioning stimulation through music or white noise listening in a sample of healthy subjects performing a Line Bisection Task (LBT). The combination of the cathodal stimulation with music listening resulted in a marked attentional shift toward the right hemispace, compensating thus the natural leftward bias of the baseline condition (pseudoneglect). Conversely, the anodal or sham pre-conditioning stimulations combined with either music and white noise conditioning listening did not modulate spatial attention. The efficacy of the combined stimulation (cathodal pre-conditioning and music conditioning) and the absence of any effect of the single stimulations provide a strong support to the state-dependency theory. They propose that tcDCS in combination with music listening could act as a rehabilitative tool to improve cognitive functions in the presence of neglect or other spatial disorders.